Metabolomics analysis of extracellular vesicles derived from bovine colostrum and mature milk - Sitong Zhang; Xipeng Sun; Yameng Zhang; Rong Huang; Wenyou Situ; Huaxi Yi; Lingjun Tong (Food Science of Animal Products)
Milk-derived extracellular vesicles (mEVs) derived from bovine colostrum (C-mEVs) and mature milk (M-mEVs) are known to carry bioactive molecules with significant immunomodulatory properties and biological effects. However, most research on mEVs has focused on their proteomics, lipidomics, and transcriptome, while metabolome analysis are still lacking. This study aims to explore the metabolomic profiles of C-mEVs and M-mEVs to uncover their molecular characteristics and potential biological functions. The mEVs were purified from both bovine colostrum and mature milk using ultracentrifugation combined with size exclusion chromatography. Through untargeted metabolomic analysis employing liquid chromatography-tandem mass spectrometry (LC-MS/MS), 76 differential metabolites, such as leucylproline, levonordefrin, adenine, polyglycerol esters of fatty acids, and hypoxanthine were identified. Among them, lipid-related metabolites were the most prominent. Hierarchical cluster analysis and principal component analysis revealed distinct metabolic signatures between C-mEVs and M-mEVs. Pathway enrichment analysis indicated that the metabolites were involved in purine metabolism and ABC transporter pathways, which was closely related to cancer, inflammation, gastrointestinal disorders, and metabolic diseases. The findings highlight the potential of metabolomics to provide a temporally precise and detailed snapshot of the molecular properties of mEVs, contributing valuable insights into mEVs-mediated molecular mechanisms and offering new avenues for research into their biological effects and therapeutic applications.